Comparative analysis of transverse flux generators design - Masliennikov, Andrii; Duniev, Oleksii; Yehorov, Andrii; Stamann, Mario; Dobzhanskyi, Oleksandr (Perfect Publishing, 2020)
This paper deals with the comparision of different transverse flux machine designs with disk rotor. Five designs were proposed compared to a basic design. The aim is to achieve a high level of efficiency combined with low manufacturing effort. Three-dimensional models of each design were created in ASCON KOMPAS-3D software. ANSYS Maxwell software was used to calculate the electromagnetic processes in each generators design. According to simulation results the two-rotor transverse-flux-generator is the best design.
Keywords: TFM; transverse magnetic flux generator; U-shaped core; magnetic flux; design; electromotive force; coil; permanent magnet